2010
DOI: 10.1007/s00726-010-0506-6
|View full text |Cite
|
Sign up to set email alerts
|

DomSVR: domain boundary prediction with support vector regression from sequence information alone

Abstract: Protein domains are structural and fundamental functional units of proteins. The information of protein domain boundaries is helpful in understanding the evolution, structures and functions of proteins, and also plays an important role in protein classification. In this paper, we propose a support vector regression-based method to address the problem of protein domain boundary identification based on novel input profiles extracted from AAindex database. As a result, our method achieves an average sensitivity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Improving the accuracy in predicting multidomain boundaries is a challenging task because the accuracy usually is considerably less than 40% [35]. We assessed the performances of DomHR on single-domain, two-domain, and multidomain sequences in the S1508 set (Table 3), and the results showed that our approach was a balanced predictor with an excellent ability to predict single-domain, two-domain and multidomain boundaries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Improving the accuracy in predicting multidomain boundaries is a challenging task because the accuracy usually is considerably less than 40% [35]. We assessed the performances of DomHR on single-domain, two-domain, and multidomain sequences in the S1508 set (Table 3), and the results showed that our approach was a balanced predictor with an excellent ability to predict single-domain, two-domain and multidomain boundaries.…”
Section: Resultsmentioning
confidence: 99%
“…DomSVR [35] predicted domain boundaries using SVR starting from the protein sequence alone and using only profiles generated from an AAindex database [36]. DROP [4] developed an SVM to predict domain linkers using 25 optimal features selected from a set of 3000 features including PSSMs and over 2000 physicochemical properties via a random forest algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Machine learning techniques have played very important roles in various protein-related problems, such as B-factors prediction [ 26 ], domain identification [ 27 ], function annotation [ 28 ], membrane protein type prediction [ 29 ], and protein retrieval [ 30 ]. Here we propose to use the random forest model for the binding site prediction.…”
Section: Methodsmentioning
confidence: 99%
“…All the regression tasks can be formulated as to seek an estimation function which can approximate the observations within an acceptable error range. In this study, least square support vector regression (LS-SVR), a version of SVR which can reduce the complexity of optimization processes, was adopted for the drift time prediction[33]. …”
Section: Methodsmentioning
confidence: 99%